RISE-based adaptive control of electro-hydraulic servo system with uncertain compensation - Xiaohan Yang; Yinghao Cui; Zhanhang Yuan; Jie Hang (Mathematical Biosciences and Engineering, 2023)
Electro-hydraulic servo system (EHSS) plays an important role in many industrial and military applications. However, its high-performance tracking control is still a challenging mission due to its nonlinear system dynamics and model uncertainties. In this paper, a novel adaptive robust integral method of the sign of the error (ARISE) with extended state observer (ESO) is proposed. Firstly, the nonlinear mathematical model of typical EHSS with modeling uncurtains and uncertain nonlinear is established. Then, ESO is used to estimate the state and lumped disturbance, of which the unknown parameter estimations can be updated by the novel adaptive law. Results shows that the novel controller achieves better tracking performance in maximum tracking error, average tracking error and standard deviation of the tracking error.